Effectiveness of Couple Therapy Based on Reality Therapy Approach on Marital Forgiveness and Empathy in Couples - Zargari Nejad, Mina; Susan, Alizadeh Fard; Davoodi, Abdolvahid (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study aimed to determine the effectiveness of couple therapy based on the reality therapy approach on marital empathy and marital forgiveness among couples.Methods and Materials: The research method was quasi-experimental with a pretest-posttest control group design including a follow-up phase. The statistical population consisted of all couples who referred to counseling centers in Tehran in 2023. From among the eligible individuals, 30 couples were selected using purposive sampling and were randomly assigned to two groups (15 couples in the experimental group and 15 couples in the control group). Data collection instruments included the Marital Empathy Questionnaire by Joliffe and Farrington (2006) and the Marital Forgiveness Questionnaire by Rye et al. (2001). The intervention group received nine 90-minute in-person group sessions over two months based on the reality therapy approach, while the control group received standard counseling services. Data were analyzed using SPSS version 24 and repeated measures ANOVA, adhering to statistical assumptions.Findings: The results indicated significant differences in the mean scores of marital empathy and marital forgiveness between the pretest, posttest, and follow-up phases (P < .01). These effects remained stable during the follow-up phase, indicating that couple therapy based on the reality therapy approach significantly improved marital empathy and marital forgiveness.Conclusion: Based on the findings of this study, couple therapy using the reality therapy approach can be considered an effective therapeutic method for enhancing marital forgiveness and empathy among couples